Isolation and identification of pseudomonas aeruginosa from infected sheep and detection of phosolipase C (lecithinase: Ahmed N. Mahmood and Assma H. Aljobori - Mahmood, Ahmed N. (The Iraqi Journal of Veterinary Medicine, 2015)
The current study dealt with the isolation and identification of 19 isolates (14.07%) for the period (October 2013 to January 2014) from different samples (135 samples) number of isolates belonging to Pseudomonas aeruginosa were 8 isolated from urine samples, their percentage were 33.33 % and 5 isolates from nasal swabs, (11.11%) and 4 isolated from milk samples (9.30%), 2 isolated from wound swabs (24%) and isolates from eye infection (9.09%). These isolates were identified by morphological examination and biochemical tests and API-20 NE system. The second part was the study of the antibiotic susceptibility that was carried out on 19 isolates of P. aeruginosa for 12 types of antibiotic. The results showed that isolates were resistant to 9 out of 12 antibiotics with percentage (Penicillin 100%, nalidixic acid100%, pipracillin 100%, erythromycin 68,4%, Chloramphenicol 63%, 78%, trimthoprim 73%, ceftacizidem 89%, cefitriaxon 84% and cefotaxime 89%) on the other hand most of isolates were sensitive to (epipenime, azythromycin, and polymixin). Detection of phospholipase C (Lecithinase) by agar well diffusion method on different selective media as (egg yolk agar, briliant green crystal violates lecithnase agar BCL), 12 isolates out of 19 showed a positive reaction on these media. The result depended on measurement the diameter of opacity zone produced and the blush green zone on the BCL media, the diameter of zone ranged from 8mm to 32mm. both media (EYA and BCL media is the best media for detection of phospholipase by P. aeruginosa.